Positionspapier mit konkreten Handlungsempfehlungen der DGAI und des BDA: ökologische Nachhaltigkeit in der Anästhesiologie und Intensivmedizin : Aktualisierung 2024 = Ecological Sustainability in Anaesthesiology and Intensive Care Medicine. A Position Paper with Specific Recommendations – Update 2024 - Schuster, Martin; Richter, Hannah; Pecher, Sabine; Bein, Thomas; Grüßer, Linda; Kowark, Ana; Lehmann, Ferdinand; Samwer, Charlotte; Brenner, Thorsten; Coburn, Mark (Anästhesiologie & Intensivmedizin, 2024)
The position paper entitled “Ecological sustainability in anaesthesiology and intensive care medicine” presents specific recommendations for action to achieve ecological sustainability in the field of anaesthesiology, intensive care medicine and emergency medicine. As such, it outlines the consequences of the environmental crises for the specialist area. It is based on the first position paper published in 2020 [1] and was adopted by the executive committees of the BDA and DGAI on Juy 19th, 2024.